Machinability of Polymer Foam Composites Reinforced with Oil Palm Empty Fruit Bunch (OPEFB) Fibers for Robot Car Body Applications - Rosyadan, Dafa Amrina; Arif Adlie, Taufan; Arif, Zainal (Fakultas Teknik Universitas Samudra, 2025)
Oil Palm Empty Fruit Bunches (OPEFB) is one of the solid wastes of the palm oil industry that is used as an alternative material to replace composite products. Composite is a material that is formed from a combination of two or more materials so that a composite material is produced that has different mechanical properties and characteristics from the forming material. This research aims to make the body of a food delivery car robot and obtain the characteristics of being able to machine (Drilling and Sawing), The test material used is a foamed polymer composite material reinforced with OPEFB fiber. The composite manufacturing process is carried out by the hand lay-up method. This test was carried out using 3 variations of drill bits with diameters of 4 mm, 6 mm, and 8 mm and by using cutting speeds of 20 m/min, 40 m/min, and 60 m/min. From the results of the comparison, the use of drill bits with a diameter of 8 mm obtained the most optimal results, where a cutting speed of 20 m/min produced a rotation speed of 796.17 rpm, a cutting speed of 40 m/min produced a rotation speed of 1592.3 rpm, and a cutting speed of 60 m/min produced a rotation speed of 2388.5 rpm. The greater the cutting speed, the greater the spindle rotation produced; the low cutting speed followed by the low spindle rotation does not raise the cutting force enough so that the composite plane will break.